Priorities for Research to Reduce the Threat of Firearm-Related Violence - Council, National Research; Education, Division of Behavioral and Social Sciences and; Justice, Committee on Law and; Medicine, Institute of; Executive Office, Institute of Medicine; Violence, Committee on Priorities for a Public Health Research Agenda to Reduce the Threat of Firearm-Related; Kelley, Patrick W; McCoy, Margaret A; Lee, Arlene F; Altevogt, Bruce M (National Academies Press, 2013)
In 2010, more than 105,000 people were injured or killed in the United States as the result of a firearm-related incident. Recent, highly publicized, tragic mass shootings in Newtown, CT; Aurora, CO; Oak Creek, WI; and Tucson, AZ, have sharpened the American public's interest in protecting our children and communities from the harmful effects of firearm violence. While many Americans legally use firearms for a variety of activities, fatal and nonfatal firearm violence poses a serious threat to public safety and welfare. In January 2013, President Barack Obama issued 23 executive orders directing federal agencies to improve knowledge of the causes of firearm violence, what might help prevent it, and how to minimize its burden on public health. One of these orders directed the Centers for Disease Control and Prevention (CDC) to, along with other federal agencies, immediately begin identifying the most pressing problems in firearm violence research. The CDC and the CDC Foundation asked the IOM, in collaboration with the National Research Council, to convene a committee tasked with developing a potential research agenda that focuses on the causes of, possible interventions to, and strategies to minimize the burden of firearm-related violence. Priorities for Research to Reduce the Threat of Firearm-Related Violence focuses on the characteristics of firearm violence, risk and protective factors, interventions and strategies, the impact of gun safety technology, and the influence of video games and other media.